Richard Shuckburgh papers - Shuckburgh, Richard, 1728-1773.; Johnson, William, Sir, 1715-1774.
Transcripts of letters and excerpts from letters of or pertaining to Shuckburgh from the papers of Sir William Johnson, British army officer and superintendent of Indian affairs in Albany, N.Y.
Typewritten transcripts made for O. G. Souneck.
British public official and physician.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Great Britain. -- Army -- Colonial forces -- New York (State); Indians of North America -- New York (State); Indians of North America -- Government relations; Albany (N.Y.) -- History -- Colonial period, ca. 1600-1775.; Great Britain -- Colonies -- America; New York (State) -- History -- Colonial period, ca. 1600-1775.; Physicians; Public officials -- Great Britain